PENGARUH MOTIVASI PIMPINAN, DISIPLIN KERJA, DAN PENGENDALIAN INTERNAL TERHADAP KINERJA PEGAWAI DI KANTOR BERSAMA SAMSAT PAMEKASAN - jurnalmap map; Moh Hosnan Syaffih; Muninghar ÔÇÄ; Fatimah Riswati (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted in Joint Office Samsat Pamekasan with the number of research samples as many as 34 employees. The purpose of this study is 1) To describe the motivation of leadership, work discipline, internal control on the performance of employees, 2) To test and analyze the motivation of leadership partially significant effect on the performance of employees, 3) To test and analyze the work discipline partially significant effect on the performance of employees. The results showed that the motivation of leadership, work discipline, and internal control simultaneously have a significant influence and have a very significant effect on improving employee performance. Leaders motivation, work discipline, and internal control individually / partially have a significant and significant influence in improving employee performance. So it can be concluded that each independent variable in this study both have an effect on the performance of employees. Keywords: leadership motivation, work discipline, internal control, employee performance